The predictive validity of a single leg bridge test for hamstring injuries in football players - Freckleton, G.; Pizzari, T.; Cook, J.; Young, M. (Journal of Science and Medicine in Sport, 2011)
Introduction: Hamstring muscle strain injury (HMSI) is the biggest injury problem in the Australian Football League (AFL). Hamstring injuries were the most prevalent injury during the 2009 season, with 7.1 new injuries per club in the 2009 season and 17% of athletes who sustained a hamstring injury suffering a recurrent strain in the same year. A recent systematic review and meta-analysis conducted by the investigators discovered quadriceps peak torque, increasing age and previous history of HMSI to be risk factors for HMSI, while limb dominance, playing position, ethnicity, dorsiflexion range of motion (ROM) and previous knee injury had inconclusive evidence. Screening of risk for hamstring tears is limited and it has been proposed that the single leg hamstring bridge test could be a useful screening test in Australian Football. This research aims to determine if a single leg bridge test can predict the risk of HMSI in amateur and sub-elite Australian Football players. Method: The project is a prospective cross-sectional design that includes 488 football players (mean age=20.7 yrs, range=16-34). All players performed the single leg bridge test during the 2011 preseason and are currently being monitored during the playing season for the incidence of a HMSI and any recurrences. The single leg bridge test involved the player placing one leg (slightly bent) onto a 60cm height box and performing repetitions of a bridging motion with full hip extension of the test leg until failure. Univariate analysis using odds ratio and 95% confidence intervals will be used to predict independent risk factors for HMSI. Results: Mean single leg bridge repetitions for the group were: left leg 26.1 (SD=10.1), right leg 25.7 (SD=9.8). Players with previous right-sided HMSI (n=64) recorded significantly less repetitions on the right leg (p<0.01) and those with previous left-sided HMSI (n=60) recorded significantly fewer repetitions of the left (p<0.01). The predictive validity of the single leg bridge test will be calculated and presented at the conference once the incidence of HMSI is known at the conclusion of the current season. Conclusion: The single leg bridge test is a screening test promoted in Australian Football as a simple method of identifying hamstring strength deficits and potentially predicting the likelihood of sustaining a HMSI. This research will shed light on the predictive validity of the test.